The core fungal microbiome of banana (Musa spp.) - Birt, Henry W. G.; Pattison, Anthony B.; Skarshewski, Adam; Daniells, Jeff; Raghavendra, Anil; Dennis, Paul G. (Frontiers in Microbiology, 2023)
Here, we report a metabarcoding (ITS2) study to define the common core fungal microbiome (mycobiome) of healthy Musa spp. (bananas and plantains). To identify our list of 21 core fungal taxa, we first characterised the effects of edaphic conditions and host genotype – two factors that are likely to differ between farms – on the diversity of fungal communities in bulk soil and seven plant compartments. This experiment facilitated shortlisting of core ‘candidates’, which were then elevated to full core status if also found to frequent a wide-range of field-grown Musa spp. and exhibit hub-like characteristics in network analyses. We then demonstrated through a meta-analysis of eleven publicly available datasets of Musa spp.-associated fungi that they have close relatives in other countries. The diversity and composition of mycobiomes differed between plant compartments and soils, but not genotypes. The core mycobiome included Fusarium oxysporum and its relatives, which dominated all plant compartments, as well as members of the Sordariomycetes, Dothideomycetes, and Mortierellomycota. Our study provides a robust list of common core fungal taxa for Musa spp. Further studies may consider how changes in the frequencies and activities of these taxa influence host fitness and whether they can be managed to improve banana production.